ACTUALIZE THE ISLAMIC EDUCATION VALUES IN TRAFFIC DISCIPLINE - Aidil Fitri (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
Islamic education not only encompasses the sheer worship. The religious values of Islam are capable of covering all human activities. However, a Moslem makes use of his/her religion when dealing with his/her God. Conversely, when interacting with the environment either by humans or animals, these Islamic values are abandoned, including when on highway. As a religion of Rahmatan Lilalamin, a Moslem should necessarily be able to bring Islam to the benefit of the universe. On the highway, a Moslem should be able to demonstrate the Islamic behavior and prevent from having diverging behavior which is contrasted to Islamic values. Adherence to traffic regulations and laws should completely be reflected while on the highway. Islam has explained by its scripture, that human existence on this earth is not only to be submissive and obedient to the laws of religion, but there are government laws which are mandatory for all human beings to obey, as an effort to establish a peaceful earth. A Moslem should become a pioneer of discipline on the highway when a lot of people ignore the applicable regulations. A Moslem should be served as an example of traffic turmoil and chaos when on highway. A Moslem should convey the values of Islam to the fellow Moslems and the followers of different religions, anytime and anywhere including on highway.